2021
DOI: 10.1177/0734242x211048125
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of amending the Amager Bakke incineration plant in Copenhagen with carbon capture and storage

Abstract: Amending municipal solid waste incineration with carbon capture and storage (CCS) is a new approach that can reduce the climate change impacts of waste incineration. This study provides a detailed analysis of the consequences of amending the new Amager Bakke incinerator in Copenhagen (capacity: 600,000 tonnes waste per year) with CCS as a post-combustion technology. Emphasis is on the changes in the energy flows and outputs as well as the environmental performance of the plant; the latter is assessed by life c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…LCA is a standardized method (see ISO 14040 & 14044 [8], [9]) and has been used multiple times in the literature to assess CCTS chains. The reduction potential has been shown for CCTS chains where CO2 is transported via pipelines and captured from flue gases of fossil fuel and wood combustion [10], waste incineration [11], as well as from geothermal fluids of geothermal power plants [12]. Similarly, it is shown that capturing CO2 from clinker production can improve the climate impact of cement if pipeline transport of CO2 is in place [10].…”
Section: Carbon Capture Transport and Storage For Net-zero Climate Goalsmentioning
confidence: 99%
“…LCA is a standardized method (see ISO 14040 & 14044 [8], [9]) and has been used multiple times in the literature to assess CCTS chains. The reduction potential has been shown for CCTS chains where CO2 is transported via pipelines and captured from flue gases of fossil fuel and wood combustion [10], waste incineration [11], as well as from geothermal fluids of geothermal power plants [12]. Similarly, it is shown that capturing CO2 from clinker production can improve the climate impact of cement if pipeline transport of CO2 is in place [10].…”
Section: Carbon Capture Transport and Storage For Net-zero Climate Goalsmentioning
confidence: 99%
“…At the Klemetsrud WtE facility in Norway, following a successful pilot project to capture 90% of direct CO 2 process emissions, development of a full-scale MEA based carbon capture of 400,000 tCO 2 /yr is underway . Amager Bakke WtE in Copenhagen, Denmark, has also established a pilot plant …”
Section: Technological Aspectsmentioning
confidence: 99%
“…Carbon in waste can be almost completely combusted into CO 2 , resulting in one tonne of CO 2 emissions per tonne of incinerated waste, making waste reduction and recycling effective methods of curbing carbon emissions. There are differences in the composition of waste, however, and it has been shown that the fossil carbon content emitted from sorted Danish waste can be as low as one-third (Bisinella et al, 2021). On the other hand, imported waste has "a significantly higher fossil share" because it contains more plastic (Danish Energy Agency, 2021, p. 8; see also Capion & Sørensen, 2021, p. 5).…”
Section: Copenhagen's Climate Plan and Decarbonisation In Waste Incin...mentioning
confidence: 99%
“…The purpose of Copenhagen's planned decarbonisation efforts, including the construction of the new waste-handling facility (Copenhill), was to avoid annual emissions of CO 2 increasing to 100,000 tonnes by 2025. Instead, new projections indicate that CO 2 emissions from Copenhill will reach 560,000 tonnes CO 2 per year by 2025 (ARC, 2021;Bisinella et al, 2021). In other words, the realised Copenhill project alone will exceed the total projected worst-case CO 2 output from waste incineration by a factor of 5.6.…”
Section: Copenhagen's Climate Plan and Decarbonisation In Waste Incin...mentioning
confidence: 99%